SOIL FERTILITY: CHALLENGES TO SOYBEAN (ð˜Žð˜ð˜ºð˜¤ð˜ªð˜¯ð˜¦ ð˜®ð˜¢ð˜¹ L.) PRODUCTIVITY IN CONSOLIDATED NO-TILLAGE SYSTEM - Kraft, Elston; Oliveira Filho, LuÃs Carlos IuÃ±es de; Maluche Baretta, Carolina Riviera Duarte; Perreira, Pierre Marcel; Spagnollo, Evandro; Wildner, Leandro do Prado; Klauber Filho, Osmar; Baretta, Dilmar (REVISTA DE AGRICULTURA, 2021)
The objective was to evaluate the relationship of soil fertility in areas with productivities gradients of soybean managed under no-tillage system (NT) in Western Santa Catarina, Brazil, and the interaction of this fertility with the physical and biological attributes of the soil. Areas with NT of High (NTH), Medium (NTM) and Low (NTL) soybean productivity were selected during the agricultural years 2016/2017 and 2017/2018. In each system, a sampling grid of 3 Ã— 3 points, positioned 30 m apart, was used. Univariate analysis of the data showed no difference between the systems. However, principal component analysis helped identify the attributes that can affect productivity. Redundancy analysis identified the influence of biological attributes on some soil nutrients. The explanation for higher soybean productivities in NT system should not consider just the chemical fertility of the soil, but a holistic approach to fertility.